2023
DOI: 10.3389/fimmu.2023.1094649
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressive effects and mechanisms of loureirin B on collagen-induced arthritis in rats

Abstract: IntroductionRheumatoid arthritis (RA) is a common disease mainly affecting joints of the hands and wrists. The discovery of autoantibodies in the serum of patients revealed that RA belonged to the autoimmune diseases and laid a theoretical basis for its immunosuppressive therapy. The pathogenesis of autoimmune diseases mainly involves abnormal activation and proliferation of effector memory T cells, which is closely related to the elevated expression of Kv1.3, a voltage-gated potassium (Kv) channel on the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Loureirin B is a flavonoid extracted from Dracaena cochinchinensis, and has a variety of pharmacological effects including promoting insulin secretion, preventing osteoporosis, and treating rheumatoid arthritis (Fang et al, 2022;Yuhao Liu et al, 2019;Zou et al, 2023). It has been reported that loureirin B can inhibit TGF-β1-induced myofibroblast differentiation in cardiac fibroblasts, thereby improving cardiac fibrosis (Cheng et al, 2022).…”
Section: Chalconementioning
confidence: 99%
“…Loureirin B is a flavonoid extracted from Dracaena cochinchinensis, and has a variety of pharmacological effects including promoting insulin secretion, preventing osteoporosis, and treating rheumatoid arthritis (Fang et al, 2022;Yuhao Liu et al, 2019;Zou et al, 2023). It has been reported that loureirin B can inhibit TGF-β1-induced myofibroblast differentiation in cardiac fibroblasts, thereby improving cardiac fibrosis (Cheng et al, 2022).…”
Section: Chalconementioning
confidence: 99%
“…1, loureirin A, loureirin B, and cochinchinenin A, belonging to dihydrochalcones, are important bioactive natural products (BNPs) found in Resina Draconis . 15 Recently, numerous studies have reported that both naturally occurring and synthetic chalcones and dihydrochalcones as anti-inflammatory agents are involved in the inhibition of cytokines and inflammatory mediator production in inflammatory disorders. 13,16–20 However, limited studies are reported on evaluating the anti-inflammatory activity of chalcones and dihydrochalcones or their structure–activity relationships (SARs).…”
Section: Introductionmentioning
confidence: 99%